The Impact of Foreign Direct Investment, Private Investment, Government Expenditure, and Labor on Economic Growth in Indonesia - Annisa, Nur; Jamal, Abd; Syahnur, Sofyan (Graha Primera Saintifika, 2025)
Sustainable economic growth is a key goal for every developing country, including Indonesia. In this context, several key factors have been identified as the main determinants influencing the pace of economic growth. This study investigates Indonesia’s economic growth in relation to foreign direct investment (FDI), private investment, government spending, and labor. The Autoregressive Distributed Lag (ARDL) method is applied to analyze time series data from 1986 to 2022. The results indicate that, in the long term, government spending has a positive and significant effect on economic growth in Indonesia, while labor has a negative effect. In the short term, FDI has a positive and significant impact on economic growth. Therefore, regulations and policies are needed in Indonesia regarding tax collection, currency stabilization, and the facilitation of permit acquisition, protection, and legal certainty.